The importance of microalbuminuria screening in persons with hypertension and with or without diabetes - Severović, Saška; Bojić, Gordana; Đorđević, Dragan (General Practice, 2025)
Introduction. Albumin is a protein produced in the liver, playing a crucial role in maintaining osmotic pressure and transporting molecules. Microalbuminuria, which is the presence of small amounts of albumin in urine, often depicts the damage to kidney function as well as the risk of developing cardiovascular and cerebrovascular diseases. Objective. We aimed to establish the prevalence of microalbuminuria in patients with hypertension and diabetes, and to estimate the prevalence in the difference between these groups and the control group. Method. The study encompassed 139 patients, separated into the exposed group (patients with hypertension and diabetes) and the control group. Microalbuminuria testing was performed using qualitative test strips. These strips detect albumin in urine. For statistical analysis, we used Chisquare - χ2 test to evaluate the difference between the groups. Results. The prevalence of microalbuminuria in the exposed group was 33,09%. Statistically significant difference in the prevalence of microalbuminuria between the exposed and the control group was confirmed with p-values below 0,05. There were no significant differences in distribution according to gender and age. Conclusion. Microalbuminuria was registered in significant percentages in patients with hypertension and diabetes, which necessitates the need for regular screening in order to timely detect changes in kidney function and calculate the risk of cardiovascular diseases.